A case of acute cerebral infarction associated with an accessory middle cerebral artery in a patient who underwent thrombectomy. Issue 1 (27th September 2019) - Deguchi, Ichiro; Osada, Takashi; Kimura, Hiroaki; Saito, Naoko; Arai, Eiichi; Kohyama, Shinya; Takao, Masaki
Abstract : Background: The accessory middle cerebral artery (AMCA) is a middle cerebral artery (MCA) anomaly originating from the anterior cerebral artery. We report our experience of a case in which thrombectomy was undertaken for a patient with hemodynamics that were specific to the AMCA. Case Presentation: An 84‐year‐old man with a history of atrial fibrillation developed paralysis of the left upper and lower extremities. Imaging examinations suggested tandem occlusion of the right internal carotid artery and the origin (M2 segment) of the right MCA. An extremely narrow MCA was visualized. Because there was concern regarding development of frontal lobe infarction, thrombectomy was carried out to restore anterograde blood flow, but an AMCA was found. Recanalization of the main MCA in the infarction zone resulted in hemorrhagic infarction, and the patient died of cerebral herniation. Conclusion: When a vascular variation like AMCA is suspected, a careful evaluation of hemodynamics is necessary before undertaking endovascular intervention. Abstract : The accessory middle cerebral artery is a middle cerebral artery anomaly originating from the anterior cerebral artery. A rare case in which thrombectomy was undertaken for a patient with hemodynamics that were specific to an accessory middle cerebral artery is reported.